Behavioral ecology of tropical birds - Stutchbury, Bridget Joan, 1962-; Morton, Eugene S. (Academic Press, 2022)
Behavioral Ecology of Tropical Birds, Second Edition provides the most updated and comprehensive review on the evolution of behavior in tropical landbirds. The book reviews gaps in our knowledge that were identified twenty years ago when the first edition was published, highlights recent discoveries that have filled those gaps, and identifies new areas in urgent need of study. It covers key topics, including timing of breeding, movement ecology, life history traits, slow vs. fast pace of life, mating systems, mate choice, territoriality, communication, biotic interactions, and conservation. Written by international experts on the behavior of tropical birds, the book explores why the tropics is a unique natural laboratory to study the evolution of bird behavior and why temperate zone species are so different. A recent surge of studies on tropical birds has helped to reduce the temperate zone bias that arose because most avian model species in behavioral ecology were adapted to northern temperate climates. This is an important resource for researchers, ecologists and conservationists who want to understand the rich and complex evolutionary history of avian behavior.